Methodological Issues in Studying Rates and Predictors of Migraine Progression and Remission. - Lipton, Richard B.; Penzien, Donald B.; Turner, Dana P.; Smitherman, Todd A; Houle, Timothy T. (Headache: The Journal of Head & Face Pain, 2013)
Background.- The progression and remission of migraine and the risk factors that determine the course of illness have been intensively studied for the past decade. Methods.- In this fourth paper in a series of methodological articles, we summarize crucial issues that influence studies of migraine clinical course, and suggest directions and opportunities for future research. Results.- Defining chronic migraine (CM) based on 15 or more headache days per month is problematic because headache frequency varies from month to month. We propose methods of defining CM as a trait and not as a state of headache frequency. Our notions of progression and remission, defined by the crossing of an arbitrary frequency boundary, are also problematic; we propose alternative approaches. Measuring headache frequency is challenging because of measurement error, temporal sampling error, and real change over time. Conclusions.- We suggest alternative approaches for defining migraine subtypes, measuring change in frequency, defining progression and remission, and modeling change over time. Our suggestions are intended to encourage dialogue and need refinement and evaluation. Our long-term goal is to improve classification and measurement to facilitate the discovery of risk factors, genes, and other biological processes that determine the onset and course of migraine.